Diary of a lonely girl, or the battle against free love - Karpilove, Miriam, 1888-1956 (Book collections on Project MUSE., 2019)
"Karpilove's Diary of a Lonely Girl was first published serially in the Yiddish daily "di Varhayt" in 1916-1918 and appeared in book form in 1918. The novel, told from the perspective of a diarist writing about her own love life, offers a raw personal criticism of radical leftist immigrant youth culture in early twentieth century New York. It boldly discusses issues of consent, body autonomy, women's empowerment and disempowerment around sexuality, courtship and politics"--